Telehealth and Telemedicine The Far-Reaching Medicine for Everyone and Everywhere - Wang, Tang-Chuan (Biomedical Engineering, 2023)
Telehealth includes clinical and non-clinical services, such as monitoring, diagnosis, and treatment, as well as delivery of preventative care and health promotion. Telemedicine is a more common term that describes remote clinical services. The major impact of COVID-19 has caused telemedicine to become mainstream since the end of 2019. Clinicians are having to use tele-consultation, tele-monitoring, tele-pharmacy, tele-rehabilitation, tele-surgery and other remote methods and technologies to assess and treat patients. In patient-centric telehealth/telemedicine, personalized data generated by the various monitoring technologies are jointly managed by patients and medical staff, moving us ever closer to the ideal of precision medicine. With contributions from many respected authors, this book incorporates updated developments as well as future prospects for the ever-expanding field of telehealth/telemedicine. It can also serve as a reference for anyone involved in this field, whether they are clinicians, researchers or patients.